Existing Health Practices in Shaping the Decision to Participate During Breast Cancer Screening Among 50-69 Years Old Women in Estonia - Kadi Lubi PhD; Kaire Sildver RM, RN, MSc; Diana Sokolova RM, RN; Vita Savicka MA; Irma Nool RN, MSc; Silja Mets-Oja RM, RN, MA; Mare Tupits RN, MSc (SAGE Publishing, 2022)
Introduction Breast cancer is easily detectable by mammography and many countries run national screening programs for women as a target group. Yet, the majority of these countries have screening participation rates below the recommended level of 70%. Objective The aim of the present article was to examine a connection between existing health practices and a decision to participate during breast cancer screening. Methods Methodologically, this research was a web panel and quantitative telephone survey. The survey was conducted among 1200 Estonian women in the age group 50-69 years. Statistical data analysis was performed with SPSS using a descriptive and logistic regression model. Results The findings revealed that among different background variables, age and existing health practices significantly influenced the decision-making for participating in the screening. Results also highlighted that the possibility to participate in the screening increased with existing supportive health practices and with the increasing age. Other sociodemographic factors did not have a significant influence on the decision-making of participation. Conclusions There is a need to educate people from an early age about the developments in health practices that could support a healthy lifestyle in terms of individual responsibility. Thus, public health campaigns should not only call for action but also focus on health education in terms of the role of preventive medicine and health practices.